Paracoccidioidomycosis mimicking adrenal cancer: a case report (Research, Society and Development, 2022)
Paracoccidioidomycosis is a pathology that presents an immense range of clinical manifestations, with fungal etiology and a significant rate of complications. The pathophysiology is related to the immune response of each host, and can be acute, subacute and chronic. The most reported clinical picture is related to pulmonary symptoms, but the characteristics can be variable because it is a hematogenous infection. There is a frequent association with workers in rural areas and a considerable relationship with males, with endemic regions in which most of the population is affected, but with the most varied clinical conditions. Diagnosis is based on microscopic visualization of fungal elements suggestive of Paracoccidioides spp. Treatment is related to the severity and symptoms presented by the individual. The aim of this study is to report a case of paracoccidioidomycosis mimicking adrenal cancer.